Anaerobic degradation of dairy wastewater in intermittent UASB reactors: influence of effluent recirculation - Couras, C. S. (2015)
This work studied the influence of effluent recirculation upon the kinetics of anaerobic degradation of dairy wastewater in the feedless phase of intermittent upflow anaerobic sludge bed (UASB) reactors. Several laboratory-scale tests were performed with different organic loads in closed circuit UASB reactors inoculated with adapted flocculent sludge. The data obtained were used for determination of specific substrate removal rates and specific methane production rates, and adjusted to kinetic models. A high initial substrate removal was observed in all tests due to adsorption of organic matter onto the anaerobic biomass which was not accompanied by biological substrate degradation as measured by methane production. Initial methane production rate was about 45% of initial soluble and colloidal substrate removal rate. This discrepancy between methane production rate and substrate removal rate was observed mainly on the first day of all experiments and was attenuated on the second day, suggesting that the feedless period of intermittent UASB reactors treating dairy wastewater should be longer than one day. Effluent recirculation expressively raised the rate of removal of soluble and colloidal substrate and methane productivity, as compared with results for similar assays in batch reactors without recirculation. The observed bed expansion was due to the biogas production and the application of effluent recirculation led to a sludge bed contraction after all the substrates were degraded. The settleability of the anaerobic sludge improved by the introduction of effluent recirculation this effect being more pronounced for the higher loads.